Training Program to Improve Self-Confidence of OSIS Members of State Senior High School (SMAN) 13 Medan - Betania Putri; Zaskia Ramadhani; Melisa Kartika; Nadine Rizki; Ghaffar Nabil; Annisa Putri; Anggrid Sarai; Adinda Sri Mayang; Eka Danta Jaya Ginting (Lembaga Yasin AlSys, 2026)
Self-confidence is an important psychological aspect of adolescent development because it influences communication skills, social participation, and the ability to express opinions. In student organizations, self-confidence supports students in taking initiative, participating actively, and carrying out organizational responsibilities. However, a Training Needs Analysis conducted among Student Council (OSIS) members at SMA Negeri 13 Medan showed that several members still experienced low self-confidence, hesitation in expressing opinions during discussions, and dependence on others’ directions. This study aims to examine the implementation of self-confidence training for OSIS members at SMA Negeri 13 Medan and analyze changes in participants’ understanding and self-confidence before and after the training. A mixed-methods approach with a pre-experimental one-group pretest–posttest design and interviews was employed. The participants comprised 39 OSIS members selected through convenience sampling. Data were collected using pretest–posttest instruments, interviews, and a self-confidence scale based on De Angelis’ theory. Quantitative data were analyzed using the Wilcoxon signed-rank test with JASP software, while qualitative data were used to support interpretation of the training implementation. The findings indicate an improvement in participants’ understanding and self-confidence after participating in the training. Participants also responded positively to the training materials, methods, and implementation process. The study concludes that self-confidence training can support students’ courage to express opinions, increase active participation, and encourage initiative in organizational activities. This study contributes to adolescent development and student organization training by demonstrating the practical value of structured self-confidence training in strengthening students’ communication readiness, organizational participation, and leadership potential.